Evaluating chemical and surface stability of thermoformed and 3D-printed clear aligners after intraoral exposure - Fabrizio Sanna; Leila Es Sebar; Isabella Sannino; Samuele Avolese; Simone Parrini; Marco Posadino; Paola Testa; Nicola Scotti; Mario Alovisi (PLoS ONE, 2026)
Introduction Align Technology, Inc. is a leading manufacturer of orthodontic aligners, using SmartTrack TM (LD30), a multilayer aromatic thermoplastic polyurethane/copolyester, and the vacuum thermoforming process. Recently, direct 3D printing using Tera Harz TC-85 DAC resin has also been explored for the production of aligners. Both aligner materials are exposed to physical and chemical aging in the oral cavity. This study evaluates the chemical aging of these materials after 7 and 14 days of exposure to the oral environment, using Optical Microscopy, Raman spectroscopy, X-ray fluorescence (XRF), and X-ray diffraction (XRD). Materials and methods Invisalign® aligners (SmartTrack TM LD30) and 3D printed aligners (Tera Harz TC-85 DAC) were worn by 20 patients for 7 ( t 1 ) and 14 days ( t 2 ). The aligners were characterized initially ( t 0 ) using Optical Microscopy, Raman spectroscopy, XRF, and XRD. After t 1 and t 2 , each aligner was reanalyzed at three locations: right and left first molars ( p 1 and p 2 ), and central incisor ( p 3 ). The results were compared with never-worn aligners ( t 0 , n = 3). Results Both materials showed high homogeneity across all locations ( p 1 , p 2 , p 3 ) and time points, indicating uniform performance after oral exposure. PCA analysis performed on Raman spectra revealed no significant chemical changes in the surface composition after 7–14 days of use. Discussion and conclusions The results demonstrated that exposure to the oral environment for up to 14 days did not significantly alter the surface chemistry of either aligner material. These findings are consistent with recent literature, suggesting that short-term intra-oral exposure does not affect aligner materials’ chemical stability.